Vaccine Development Strategy for Myiasis Caused by the Larvae of Chrysomya Bezziana (The Old World Screwworm Fly) - Muharsini, Sri (Indonesian Bulletin of Animal and Veterinary Sciences, 2005)
Indonesia is an endemic area for myasis caused by the larvae of Chrysonrya bezziana . So far, the controlling method for myiasis is using insecticides such as organophosphate and coumaphos compounds . Sterile Insect Technique (SIT) was a successful method for myiasis control, however, this method is expensive, beside it needs a large amount of insecticide. Therefore, vaccinations as an alternate controlling method for myiasis which relatively cheap, environment friendly and in accordance with the sustainable agriculture concept are needed . The strategy of myiasis vaccine development has been done by the Indonesia Research Institute for Veterinary Science in collaboration with IUC-ITB, Bandung and CSIRO, Brisbane-Australia, are briefly discussed in this paper. The first step was to identify and purify the protective antigens from excretory/secretory material and peritrophic membrane. The excretory/secretory material was purified and analysed using amino-terminal sequencing and resulted trypsin and chymotrypsin at 26 kDa and 28 kDa, respectively . The peritrophic membrane was then fractionated and resulted candidate antigens of Cb 15, Cb42 and Cb48 . The three antigens were expressed into bacterial Eschericia coli and yeast Pichia pastoris resulting different yield depending on each protein character . The strategy of myiasis vaccine could be used as an alternate way for vaccine development for other parasite diseases in Indonesia. Key words: Chrysoniya bezziana, vaccine, excretory/secretory, peritrophic membrane